Вредноста на корпоративното управување и заканата за корпоративната репутација - Павловиќ, Маја (Економски факултет, УКИМ, Скопје, 2015)
This doctorate’s thesis elaborates the complexity of the corporate governance value, and the threat of the corporate reputation, as well. Building the value of the legal entity is a hard work, but it could be knocked down throughout the night. Skills, knowledge, wisdom are prerequisites for the company to survive in the turbulent economic, legal, technological and social environment. This research addresses the current issues identified in several segments. The first segment addresses the value of the good corporate governance that is measured by the premium institutional investors are willing to pay. The transparency and financial data disclosure are necessary for good corporate governance. The second segment looks at the link between the firm value and its corporate governance. Better governed firms have more superior financial results. Major shareholders have more intensive concentration of the control, but the minor shareholders have been threaten by the expropriation of their shareholders’ rights. Family ownership creates the value only when the founder have the function of the chief executive office or chairman. The firm increase its own value upon the introduction of the investor relations. The possibility to provide the guarantee decrease the cost of external financing. The corporate governance in the ethical framework is analyzed in the third segment. Ethical leaders are active participants. Unethical behavior, as well products and services failures are the common factors of corporate reputation erosion. Managers who ignore the needs of employees and consumers, lead to lower productivity. The fourth segment addresses many problems in the shareholders’ rights area. The rise of the institutional investors adds new weight and dimension to the corporate governance. Finally, the corporate leadership is substantially worried for the nature of their reputation, and the scandals of corporate governance are numerous, that are damaging the corporate reputation. Thus, the firm should meet stakeholders’ expectations and build the long road back to reputational health.
Докторска дисертација одбранета во 2015 година на Економскиот факултет во Скопје, под менторство на проф. д–р Бобек Шуклев.
Keywords: board of directors, chief executive officer, corporate governance, corporate reputation, ethics, family business, investor relations, shareholder, value